Longitudinal relationships between workplace bullying and psychological distress - Morten Birkeland Nielsen; Jørn Hetland; Stig Berge Matthiesen; Ståle Einarsen (Nordic Association of Occupational Safety and Health (NOROSH), 2012)
OBJECTIVES: The aims of this study were to examine reciprocal longitudinal associations between exposure to workplace bullying and symptoms of psychological distress and to investigate how self-labeled victimization from bullying explains the effects of bullying on health. METHODS: Logistic regression analysis was employed to examine the longitudinal relationships between workplace bullying and psychological distress in a representative cohort sample of 1775 Norwegian employees. The time-lag between baseline and follow-up was two years. Exposure to bullying behavior was measured with the revised version of the Negative Acts Questionnaire. Perceived victimization from bullying was measured by a single self-labeling question. Psychological distress was measured with the 25-item Hopkins Symptom Checklist. All variables were measured at both baseline and follow-up. RESULTS: After adjustment for psychological distress at baseline, exposure to bullying behavior [odds ratio (OR) 1.68, 95% confidence interval (95% CI) 1.07-2.62) was found to predict subsequent psychological distress. This effect of bullying behaviors disappeared when victimization from bullying (OR 2.47, 95% CI 1.17-5.22) was entered into the regression. Both psychological distress (OR 2.49, 95% CI 1.64-3.80) and victimization (OR 2.61, 95% CI 1.42-4.81) at baseline were associated with increased risks of being a target of bullying behaviors at follow-up. Psychological distress (OR 2.51, 95% CI 1.39-4.52) and bullying behaviors (OR 2.95, 95% CI 1.39-4.52) at follow-up were associated with victimization. CONCLUSION: The mutual relationship between bullying and psychological distress indicates a vicious circle where bullying and distress reinforce their own negative effects. This highlights the importance of early interventions to stop workplace bullying and provide treatment options to employees with psychological distress.